COMPOSITIONS OF TERNARY RELATIONS - Norelhouda Bakri; Lemnaouar Zedam; Bernard De Baets (Université de M'sila, 2021)
In this paper, we introduce six basic types of composition of ternary relations, four of which are associative. These compositions are based on two types of composition of a ternary relation with a binary relation recently introduced by Zedam et al. We study the properties of these compositions, in particular the link with the usual composition of binary relations through the use of the operations of projection and cylindrical extension
Keywords: binary relation, ternary relation, relational compositions